COTI-2 induces cell apoptosis in pediatric acute lymphoblastic leukemia via upregulation of miR-203 - Guo, Yingmeng (Bioengineered, 2020)
COTI-2 is a third-generation thiosemicarbazone, which is effective against a diverse group of human cancer cell lines at nanomolar concentrations. COTI-2 also showed superior activity against tumor cells, in vitro and in vivo. As a high efficacy and low toxicity agent, it currently candidates in a phase I clinical study of gynecological malignancies and head and neck squamous cell carcinoma (HNSCC). However, its effect in pediatric T-cell acute lymphoblastic leukemia (T-ALL) is not clear. This study investigates the effect of COTI-2 on T-ALL Jurkat cells in vitro and in vivo. Jurkat cells were exposure to COTI-2 at different concentration and time. Cell apoptosis was detected by flow cytometry to examine the sensitivity of Jurkat cell lines treated with either COTI-2 alone or in combination with MiR-203 mimic or inhibitor in vitro. An orthotopic mouse model was used to examine the sensitivity of Jurkat cells treated with COTI-2 in vivo. Western blotting and RT-qPCR were performed to dissect molecular mechanisms. The results showed that COTI-2 promotes apoptosis of Jurkat cells in dose-and time-dependent way. Enforced expression of miR-203 promotes COTI-2-mediated cell apoptosis, whereas miR-203 silencing attenuates COTI-2-mediated cell apoptosis in Jurkat cells in vitro. COTI-2 is also effective against growth of Jurkat cells in vivo. Mechanistically, COTI-2 induced miR-203 upregulation and inhibited caspase-3/9 activaty leading to inhibition of cell apoptosis. Taken together, COTI-2 inhibits tumor growth in vitro and in vivo in Jurkat cells likely through miR-203-dependent mechanisms. COTI-2 may be a potential approach for T-ALL treatment.